Hole Transport Layer Free Perovskite Light-Emitting Diodes With High-Brightness and Air-Stability Based on Solution-Processed CsPbBr3-Cs4PbBr6 Composites Films - Yuan, Fang; Zhang, Min; Zhu, Chunrong; Liu, Xiaoyun; Zhao, Chenjing; Dai, Jinfei; Dong, Hua; Jiao, Bo; Lan, Xuguang; Wu, Zhaoxin (Frontiers in Chemistry, 2022)
Recently, perovskite light-emitting diodes (PeLEDs) have drew widespread attention due to their high efficiencies. However, because of the sensitivity to moisture and oxygen, perovskite luminescent layers are usually prepared in high-purity nitrogen environment, which increases the cost and process complexity of device preparation and seriously hindrances its commercialization of PeLED in lighting and display application. Herein, dual-phase all-inorganic composite CsPbBr3-Cs4PbBr6 films are fabricated from CsBr-rich perovskite solutions by a simple one-step spin-coating method in the air with high humidity. Compared with the pure CsPbBr3 film, the composite CsPbBr3-Cs4PbBr6 film has much stronger photoluminescence emission and longer fluorescence lifetime, accompanied by increased photoluminescence quantum yield (33 %). As a result, we obtained green PeLED devices without hole transport layer exhibiting a maximum brightness of 72082 cd/m2 and a maximum external quantum efficiency of about 2.45%, respectively. More importantly, the champion device shows excellent stability with operational half-lifetime exceeding 1000 min under continuous operation in the air. The dual-phase all-inorganic composite CsPbBr3-Cs4PbBr6 film shows attractive prospect for advanced light emission applications.